Insight into the Selectivity of the G7-18NATE Inhibitor Peptide for the Grb7-SH2 Domain Target - Watson, Gabrielle M.; Lucas, William A. H.; Gunzburg, Menachem J.; Wilce, Jacqueline A. (Frontiers in Molecular Biosciences, 2017)
Growth factor receptor bound protein 7 (Grb7) is an adaptor protein with established roles in the progression of both breast and pancreatic cancers. Through its C-terminal SH2 domain, Grb7 binds to phosphorylated tyrosine kinases to promote proliferative and migratory signalling. Here, we investigated the molecular basis for the specificity of a Grb7 SH2-domain targeted peptide inhibitor. We identified that arginine 462 in the BC loop is unique to Grb7 compared to Grb2, another SH2 domain bearing protein that shares the same consensus binding motif as Grb7. Using surface plasmon resonance we demonstrated that Grb7-SH2 binding to G7-18NATE is reduced 3.3-fold when the arginine is mutated to the corresponding Grb2 amino acid. The reverse mutation in Grb2-SH2 (serine to arginine), however, was insufficient to restore binding of G7-18NATE to Grb2-SH2. Further, using a microarray, we confirmed that G7-18NATE is specific for Grb7 over a panel of 79 SH2 domains, and identified that leucine at the D6 position may also be a requirement for Grb7-SH2 binding. This study provides insight into the specificity defining features of Grb7 for the inhibitor molecule G7-18NATE, that will assist in the development of improved Grb7 targeted inhibitors.